2016
DOI: 10.1159/000447948
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Indices May Be Useful in the Diagnosis of Systemic Lupus Erythematosus and in Determining Disease Activity in Behçet's Disease

Abstract: Objectives: The aim of this study was to investigate the relationships between clinical features of rheumatic diseases and hematologic indices, including mean platelet volume (MPV), MPV/platelet ratio (MPR), platelet/lymphocyte ratio, and neutrophil/lymphocyte ratio (NLR). Subjects andMethods: Rheumatoid arthritis (RA; n = 91), systemic lupus erythematosus (SLE; n = 51), systemic sclerosis (SSc; n = 39), and Behçet's disease (BD; n = 53) patients, and 55 healthy controls (HC) were enrolled. Hematological indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 24 publications
4
79
3
Order By: Relevance
“…After reading this article, I have the following suggestions: I think it would be good if the title were more specific (perhaps including such terms as “platelet size” or “platelet volume”).Contrary to what is mentioned in the last paragraph of the Introduction, Rupa-Matysek et al 1 did not include SLE patients in their study.Our team also published an article on this topic 2 , which is not mentioned in the Introduction, even when it appeared online before that of Yolbas et al 3 .I would like to know if the sampling technique was consecutive or random. I'm inclined to think that consecutive (i.e., non-random) sampling was used.…”
mentioning
confidence: 96%
“…After reading this article, I have the following suggestions: I think it would be good if the title were more specific (perhaps including such terms as “platelet size” or “platelet volume”).Contrary to what is mentioned in the last paragraph of the Introduction, Rupa-Matysek et al 1 did not include SLE patients in their study.Our team also published an article on this topic 2 , which is not mentioned in the Introduction, even when it appeared online before that of Yolbas et al 3 .I would like to know if the sampling technique was consecutive or random. I'm inclined to think that consecutive (i.e., non-random) sampling was used.…”
mentioning
confidence: 96%
“…One of these was excluded because they included other diseases [31]. Thus, nine articles met the inclusion criteria [3,[10][11][12][13][14][15][16][17] (Table 1, Figure 1). One report contained data on two different groups [12], so we analyzed these studies independently.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…Recent studies have reported the numbers and ratios of complete blood cell (CBC) subgroups in rheumatic diseases [3,4]. Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and mean platelet volume (MPV) have recently been investigated as new inflammatory markers for the assessment of inflammation in many inflammatory, cardiovascular, and malignant diseases [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haematological studies are useful for the diagnosis of both human and animal diseases as well as investigation of the extent of damage to blood [20][21][22]. Haematological profile evaluations are important in assessing the health status of dogs infected with GI helminths [23].…”
Section: Dog Hookworm Also Called Ancylostoma Caninum (A Caninum)mentioning
confidence: 99%